Samshodhana Mandala: An Important ’Private Library’ in Nepal - Paudel, Kishor; Nyaichyai, Lila (Access: An International Journal of Nepal Library Association, 2023)
The paper deals with the private library of Dr. Mahes Raj Pant. This study aims to explore his private library status and the reasons behind his enormous collections. Some reports have shown that private libraries in Nepal are expanding and this paper explain son what kinds of collections they have in their collections, how they are organized, the future aim for their library and etc. In Nepalese history, private collectors have greatly aided in the growth of national collections. So, if the government is interested in preserving valuable documents of this library or allowing the authority to run it, this study gives light to such a potentiality.